STRATEGIES FOR IMPROVING REPRODUCTIVE EFFICIENCY OF POSTPARTUM ANESTRUS SURTI BUFFALOES - PARMAR, K H; SHAH, R G; TANK, P H; DHAMI, A J (The Indian Journal of Animal Reproduction, 2023)
The study was conducted at three village co-operative societies of Panchmahal district in Gujarat during the months of January to June, 2011. The postpartum anestrus buffaloes (n=52) were dewormed using Fenbendazole 3 g and then were randomly divided into four groups, viz., Gr-A) Supplementation of Chelated mineral mixture, orally@ 30 g/day/animal for one month (n=14), Gr-B) lnj. inorganic phosphorus and lnj. vitamin AD3E 10 ml each, i/m (n=14) at weekly interval for three consecutive weeks, Gr-C) lnj. GnRH (Receptal) 5.0 ml, i/m once (n=12), and Gr-D) untreated control (n=12). The highest conception rate (80.00 %), shortest service period (123.60 ± 2.69 days) and highest reproductive efficiency (66.66 % ) was observed for group-C buffaloes follow by group B, A and control group, The corresponding values for group-B were 71.42 per cent, 128.71 ± 1.93 days and 35.71 per cent, and for group-A 66.66 per cent, 137 .83 ± 2.63 days and 28.56 per cent respectively. Injection of Receptal had beneficial effect on reproductive performance with improved conception rate and reduced service period as compared to other treatments and control group of anoestrus buffaloes.